Structure and processes of interdisciplinary geriatric consultation teams in acute care hospitals: A scoping review. (March 2016) - Deschodt, Mieke; Claes, Veerle; Van Grootven, Bastiaan; Van den Heede, Koen; Flamaing, Johan; Boland, Benoit; Milisen, Koen
Abstract: Background and objectives: Interdisciplinary geriatric consultation teams are implemented in the acute hospital setting in several high-income countries to provide comprehensive geriatric assessment for the increasing numbers of older patients with a geriatric profile hospitalized on non-geriatric units. Given the inconclusive evidence on this care model's effectiveness to improve patient outcomes, health care policy and practice oriented recommendations to redesign the structure and process of care provided by interdisciplinary geriatric consultation teams are needed. A scoping review was conducted to explore the structure and processes of interdisciplinary geriatric consultation teams in an international context. As nurses are considered key members of these teams, their roles and responsibilities were specifically explored. Design: The revised scoping methodology framework of Arksey and O'Malley was applied. Data sources: An electronic database search in Ovid MEDLINE, CINAHL and EMBASE and a hand search were performed for the identification of descriptive and experimental studies published in English, French or Dutch until April 2014. Review methods: Thematic reporting with descriptive statistics was performed and study findings were validated through interdisciplinary expert meetings. Results: Forty-six papers reporting on 25 distinct interdisciplinary geriatric consultation teams in eight countries across three continents were included. Eight of the 12 teams (67%) reporting on their composition, stated that nurses and physicians were the main core members with head counts varying from 1 to 4 members per profession. In 80% of these teams nurses were required to have completed training in geriatrics. Advanced practice nurses were integrated in eleven out of fourteen interdisciplinary geriatric consultation teams from the USA. Only 32% of teams used formal screening to identify patients most likely to benefit from their intervention, using heterogeneous screening methods, and scarcely providing information on the responsibilities of nurses. Nurses were involved in the medical, functional, psychological and social assessment of patients in 68% of teams, either in a leading role or in collaboration with other professions. Responsibilities of interdisciplinary geriatric consultation teams' nurses regarding in-hospital follow-up or transitional care at hospital discharge were infrequently specified (16% of teams). Conclusions: This scoping review identified that the structure and processes of care provided to geriatric patients by interdisciplinary geriatric consultation teams are highly heterogeneous. Despite nurses being key team members, only limited information on their specific roles and responsibilities was identified. More research in this area is required in order to inform health care policy and to formulate practice oriented recommendations to redesign the interdisciplinary geriatric consultation team care model aiming to improve its effectiveness.